2014
DOI: 10.1080/00222933.2013.826830
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional characterization and antibacterial activity of haemocytes fromOctopus vulgaris

Abstract: This study focused on the morphological and functional characterization of the haemocytes from Octopus vulgaris as the first agents responsible for innate immunity. Three major haemocytes types were identified by light microscopy based on nucleus/cytoplasm ratio and the presence or absence of cytoplasm granules: haemoblast-like cells, hyalinocytes and granulocytes. The presence of three haemocyte populations was also confirmed by flow cytometry. Cytochemical characterization suggests that they perform differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 49 publications
0
23
0
Order By: Relevance
“…In addition, hemocyte cells from O. vulgaris were developed in a novel growth medium in which researchers have studied its antimicrobial activity and have differentiated and characterized their hemocyte cells using staining and flow cytometry (Troncone et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, hemocyte cells from O. vulgaris were developed in a novel growth medium in which researchers have studied its antimicrobial activity and have differentiated and characterized their hemocyte cells using staining and flow cytometry (Troncone et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Troncone et al. ). In these systems, hemocytes were morphologically differentiated and antibacterial activity was estimated by using various gram positive and gram negative bacteria (Troncone et al.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…13. Troncone et al (2014) identified three hemocyte types in octopus; granulocytes, hyalinocytes and haemoblastlike cells. The granulocytes are able to extend pseudopodia.…”
Section: Histological Structure Of the White Body (The Hematopoietic mentioning
confidence: 99%
“…Haemocytes are crucial in the cephalopod immune response [51,52,53]. Although these cells are vital to maintain the wellbeing in all different cephalopod species, the studies conducted about haemocytes are limited, and most of the observations have been performed on octopus species [45,50,54,55,56,57,58] with few descriptions available on Euprymna scolopes [59] and Sepia officinalis [46,60,61]. In one of the first studies of characterization based on morphology and immune capability of cells, Stuart [49], identified phagocytic and non-phagocytic "leucoblastic cells" in common octopus.…”
Section: Type and Number Of Haemocytes In The Cephalopods Haemolymphmentioning
confidence: 99%